Corrosion inhibition and adsorption studies by Pogostemonquadrifolius methanolic stem extract (PQMSE) on mild steel in 1M HCL - M, Jisha; Hukuman N. H, Zeinul; P, Leena (International Journal of Advanced Chemistry, 2018)
Pogostemon quadrifolius methanolic stem extract (PQMSE) has been investigated as non toxic green corrosion inhibitor for mild steel in 1 M HCl. Corrosion rates were evaluated at 303 K, 313 K and 323 K by weight loss method at varying inhibitor concentrations. Using electrochemical impedence spectroscopy (EIS) and polarisation techniques, corrosion studies were done at 303 K in various inhibitor concentrations. Adsorption studies were also conducted to study the mechanism of corrosion inhibition. Scanning electron microscopy (SEM) and Fourier – transform infrared (FT-IR) spectroscopy were used to study the surface morphology of mild steel. Electrochemical studies reveal that PQMSE exhibit excellent corrosion inhibition efficiency and it function as a mixed type of inhibitor at 303 K. The surface interaction of PQMSE on mild steel in 1 M HCl was obeying Langmiur adsorption isotherm at all studied temperatures.